Effects of the Random Diagonal code link parameters on the performance of an OCDMA scheme for high-speed access networks - Hilal Adnan, Fadhil; Syed Alwee Aljunid, Syed Junid; R.Badlishah, Ahmad (Elsevier Inc., 2009)
Link to publisher's homepage at http://www.elsevier.com